Itchy Blisters and Pink Bumps on the Hands and Elbows. Issue 5 (September 2016) - So, Jessica Kim; Jacob, Sharon E.
Abstract : ABSTRACT: Teledermatology is a term to describe the provision of dermatologic medical services through telecommunication technology. In this modality, there is transfer of patient medical information electronically (including history and visual data) obtained in one location to a provider who is in another location (Roman & Jacob, 2015). The construct of the TeleDermViewPoint column is such that cases are presented in a standardized teledermatology reader format reflective of an actual teledermatology report. This is a case of itchy blisters and pink bumps on the hands and elbows.